Genetic variation in transferrin as a predictor for differentiation and evolution of caribou from eastern Canada - Røed, Knut H.; Ferguson, Michael A. D.; Crête, Michel; Bergerud, Tom A. (Rangifer, 1991)
Polycrylamide gel electrophoresis was used to analyse tranferrrin variation in caribou populations from Manitoba, Ontario, Québec/Labrador, and from Baffin Island, Northwest Territories in eastern Canada. The transferrin allele frequencies in these populations were compared with those previously reported for Canadian barren-ground caribou, Rangifer tarandus groenlandicus, Alaska caribou, R.t. grand, Peary caribou, R.t. pearyi, Svalbard reindeer, R.t. pla-tyrhynchus, and Eurasian tundra reindeer, R.t. tarandus. A total of twenty different alleles was detected in the analysed material, considerable genetic heterogeneity being detected among regions. Three alleles that were relatively common in caribou from Ontario, Manitoba and Québec/Labrador, were not present in R.t. grand, R.t. pearyi, R.t. tarandus or R.t. platyrhynchus, and present only at very low frequencies 'm R.t. groenlandicus. These findings, together with genetic identity analyses, suggest that the caribou in Manitoba, Ontario, and Québec/Labrador are mainly of the R.t. caribou type, and that little interbreeding has occurred with other subspecies. The large genetic distance in the transferrin locus between R.t. caribou and other subspecies of reindeer/caribou suggests that, during the Wisconsin glaciation the ancestral populations of R.t. caribou survived in a refugium different from that of the ancestral populations of the other subspecies. Significant genetic differences between Baffin Island caribou and all other populations were mainly due to the presence of one allele that was in high frequency in Baffin Island caribou, but that was absent, or present in very low frequencies, in all other reindeer/caribou populations. The genetic differences between Baffin Island caribou and the other subspecies were greater than the differences between several of the currently recognized subspecies.